Suomen nominien taivutusjärjestelmän produktiivisuuden indekseistä - Nikolaev, Alexandre; Niemi, Jussi (Virittäjä, 2008)
Indices of productivity in Finnish inflection (englanti) 4/2008 (112) Indices of productivity in Finnish inflection The aim of the present study is to describe how productivity is manifested in the inflection of Finnish nominals (i.e. nouns and inflectionally noun-like syntactic categories), when productivity is analysed with the help of different linguistic variables. The goals of the study also include the quantification of productivity in morphological systems that are typologically similar to that of Finnish, i.e. to attempt to obtain responses to such questions as how the productivity of an inflectional category is reflected in the Finnish inflectional system, and how many indices of productivity there are. In addition, the study includes an analysis of potential, quantifiable interaction between these various indices. In each inflectional category, the authors examine the relationship between category size and frequency of use (lemma frequency) by using regression analysis. The variables include lexical factors (e.g. median of lemma frequency, number of hapaxes) as well as a phonological factor, namely the number of syllables. The reliability of the present results is enhanced by the relatively large size of the data: the study employs the paradigm classification found in two extensive monolingual dictionaries, viz. Suomen kielen perussanakirja and CD-Perussanakirja with their 49 nominal paradigms, circa 25,000 lexemes and 52,000 compounds, as well as the corpora of the Language Bank (of Finland; www.csc.fi) containing over 130 million running words. The central conclusion is that there exists a strong correlation between paradigm size and the frequency of use of a given word in Finnish (and, presumably, in all typologically similar languages too) as follows: productive paradigms are extensive and they are characterised by low frequency of use, while unproductive paradigms are narrow but their frequency of use is high. In addition, the authors applied the formulae developed by Harald Baayen (e.g. Baayen 2003) to the frozen paradigms and to those that are not unambiguously productive. Alexandre Nikolaev Jussi Niemi - - - - - - - - - - - - Suomen nominien taivutusjrjestelmn produktiivisuuden indekseist Tutkimuksemme kuvaa sit, miten produktiivisuus ilmenee suomen nominaalisessa taivutusjrjestelmss, kun sit tarkastellaan erilaisten kielellisten muuttujien avulla. Yhten tarkoituksenamme on mys kvantifioida produktiivisuuden ksitett suomen kielen tapaisissa morfologisissa jrjestelmiss. Etsimme siis vastauksia kysymyksiin, miten taivutustyyppien produktiivisuus ilmenee suomen kielen taivutusjrjestelmss, kuinka paljon produktiivisuuden indeksej on ja onko niiden vlill vuorovaikutusta, jota voisi mitata jollakin tavalla. Tarkastelemme tyypin laajuuden ja kyttyleisyyden (lemmataajuuden) suhdetta kunkin taivutustyypin kohdalla soveltamalla nihin regressioanalyysi. Selittjin kytmme sek leksikaalisia tekijit, mm. lemmataajuuden mediaania ja hapaksien mr (korpuksessa kerran esiintyvien sanojen mr), ett fonologista tekij eli tavujen mr. Tilastollisten testiemme luotettavuutta tukee aineiston verrattain laaja koko: kytmme nimittin Suomen kielen perussanakirjan ja CD-Perussanakirjan paradigmaklassifikaatiota (49 nominaalista paradigmaa, noin 25000 lekseemi ja 52000 yhdyssanaa) sek Kielipankin (www.csc.fi) suomenkielisi korpuksia (yli 130 milj. sanetta). Ptuloksena on se, ett suomessa (ja oletettavasti muissa typologisesti samantapaisissa kieliss) taivutustyypin laajuus ja sanan kyttyleisyys korreloivat vahvasti keskenn siten, ett kun produktiivinen taivutustyyppi on laaja, sille on ominaista keskimrin alhainen kyttyleisyys. Toisaalta, epproduktiivinen taivutustyyppi on suppea ja sen kyttyleisyys on korkea. Laskimme morfologisen produktiivisuuden asteet mys muille kuin selvsti produktiivisille ja kivettyneille taivutustyypeille soveltamalla aineistoon Baayenin (esim. 2003) kaavoja. Alexandre Nikolaev Jussi Niemi